Konsentrasi Industri dan Price Cost Margin pada Industri Kendaraan Bermotor di Indonesia Studi Kasus 2001-2005 - Marpaung, Sofia Carolina (Jurnal Manajemen Akuntansi (JUMSI), 2024)
The Motor Vehicle Industry in Indonesia is a mainstay sector of the national economy because it contributes a huge investment value and employment. Therefore, this study wants to analyze the concentration of industry and its relationship with the price-cost margin of the motor vehicle industry in Indonesia in 2001-2005. This study uses large and Medium Industries (IBM) data obtained from the Indonesian Central Bureau of Statistics, which is classified by five digits of the Indonesian Lapngan Standard Classification (KBLI). The results showed a significant effect if the concentration using CR4 and no significant effect by using HHI.